The Impact of Chatbot-Driven Artificial Intelligence in Improving Students' Vocabulary - Dillon, Bobby Pramjit Singh; Ambarita, Prini Desima Evawani; Hutauruk, Bertaria Sohnata (Akademika, 2025)
This study explores how effective AI chatbots enhance students’ vocabulary skills at Nommensen University in Pematangsiantar. Emphasizing the importance of vocabulary in English education, this study uses qualitative methods, including interviews and student documentation, with 25 participants from a third-semester English Vocabulary class. To analyze the data, the authors apply thematic analysis to identify patterns and themes within the interview responses and a 5-point Likert scale to gauge students’ perceptions. The findings reveal that AI chatbots significantly enhance students’ English vocabulary learning experience. Students not only enjoyed the process but also found it easier to acquire new words, which they eagerly applied in their diary entries and essays. The researchers strongly advocate for English teachers to incorporate AI chatbots into their lessons, as this approach can significantly improve students’ understanding of word meanings. Additionally, they urge future researchers to delve into a wider array of language skills to further enrich the learning journey. Overall, the results indicate that AI positively affects vocabulary improvement among students. Participants were enthusiastic and motivated since the application was new to them. They also recognized its usefulness, allowing them to learn independently anytime and anywhere.